Spain : 2008 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This 2008 Article IV Consultation highlights that after 15 years of impressive growth led by a housing boom, the Spanish economy has entered a sharp downturn in the wake of the global liquidity squeeze since mid-2007. Executive Directors have commended the authorities for their timely and substantial fiscal and financial sector responses to help cushion the downturn. They have emphasized that these efforts need to be complemented by reforms to bolster competitiveness and to avoid a prolonged period of slow growth and high unemployment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet